LIBRARY SERVICE STRATEGY DURING THE COVID-19 PANDEMIC - Hasanah, Nur; Fathurrahman, Muslih (Academic Solution Publisher, 2023)
This research was conducted at the Batu Bara Regency Library Service. The aim of this research is to find out about the library service strategy during the Covid-19 pandemic at the Batu Bara Regency Library Service, to find out the supporting and inhibiting factors in carrying out library service strategies during the pandemic at the Department. Batu Bara Regency Library. The method used in this research is a qualitative research method using a descriptive approach. The data collection techniques used in this research were interviews, observation, and documentation. The results of this research show that library service strategies during the pandemic were carried out by librarians, namely by running mobile libraries, collaborating with other parties, temporary loan services, while the obstacles that occurred were by limited digital book collections, limited printed collections, limited infrastructure: IT equipment and networks, limited operational vehicles and their supporting equipment, and limited human resources who are competent in the fields of library and information and IT.